The study of blood pressure profile among school going adolescents in urban Agra - Singh, Akash K.; Misra, Sunil K.; Chaudhary, Shailendra S.; Singh, Geetu (International Journal Of Community Medicine And Public Health, 2019)
Background: Hypertension once considered a problem of adults only in the high income countries, now dramatically is on the rise in low and middle income countries. An established predictor of adult hypertension and organ damage is childhood hypertension. Thus for the control, effective treatment and prevention of its complications, early diagnosis of hypertension in adolescents in an important strategy. The objective was to study the blood pressure profile and its socio-demographic determinants among school going adolescents in urban Agra. Methods: A cross-sectional survey was done among 534 adolescent in age group of 13-18 years studying in various government and private schools in urban Agra. Socio demographic details, anthropometric measurements and family history of hypertension were obtained. Also the dietary habits, physical activity, mode of transport to school were included in the present study. Blood pressure was measured at 0 and 30 minutes and average of two readings was taken as the final reading of that individual. Results: It was found that 49.82% of the study subjects had above normal blood pressure and among them 21.16% were hypertensive and 28.66% had pre-hypertension. Higher blood pressure showed a statistically significant (p<0.05) association with gender, age, dietary habits, physical activity, body mass index, and parental history of hypertension. Conclusions: Hypertension among the adolescent age group was very high. Prevalence of high blood pressure significantly associated with age, gender, family history of hypertension, physical activity, type of school and dietary habits.